DESIGNING EDUCATION COMIC STRIPS AS SUPPLEMENTARY MATERIAL IN TEACHING MODAL VERBS OF OBLIGATION - Arismunandar, Vicky; Apriliaswati, Rahayu; Surmiyati, Surmiyati (Universitas Tanjungpura, 2024)
This research is aimed at designing education comic strips as supplementary material in teaching modal verbs of obligation for